Interactive Strategic Solution for Future Global Challenges: Multistage Systems Planning Methodology and New 8 M's Model - Heiba, F. (2011)
Growth and development have always been powerful and motivating forces for people, business and nations. One can say the old saying “you are either growing or shrinking, there is no middle ground. “The country development aims to create and implement strategies that achieve both economic and societal value for better future. One of the critical issues in learning, learning and learning, and the role of strategic thinking in the development process. Brainpower, the soft side of technology, is becoming an organizations most valuable asset and conveys a competitive edge in the market place only countries that make use of their technology, knowledge capabilities and expertise will succeed in a dynamically competitive environment and achieve desirable future development. The real challenge, however, is how to apply successfully the two side of technology (soft and hard) and focus on strategically on the priorities of development process. The 2004 Nobel prize winner in economics; professor Edward Prescott, Arizona state university, states that the difference among nations in development is on how to conduct their technology towards clear and specific objectives rather than wasting their time in criticizing the reasons for failure. Thus, Egypt, in its quest for success and desirable development, must face the real challenge of application of both sides (soft and hard) of knowledge, science and technology in the society. Life is no longer simple; one cannot anymore just hope that things will work themselves out. Egypt is challenged to become strategic thinker rather than wishful thinker, if it desires to achieve future development and ensures prosperity and modernization to its people. This research aims to provide a composite picture of the critical relationship between knowledge and technology and future development programs. In addition, an integrated strategic methodology is introduced to build the necessary requirements and what ought to be done for achieving future development of countries based on a new suggested model, the 8 M’s model for economic growth that will help in identifying development composites and elements.